Mecz bokserski : pomiędzy H.C.P. Poznań - Milic.K.S. Gdynia. (Gdynia : [s.n.], 1946)
Afisz inf. o meczu, który odbył się 1.12.1946 r. w sopockiej Miejskiej Hali Sportowej.
Keywords: Boks -- Polska -- Sopot -- 1945-1970 -- druki ulotne; Sopot (Polska) -- 1945-1970 -- druki ulotne; Sopot (Polska) -- 1945-1970 -- źródła